Training of the will - Coburn, Tina Louise (My University, 1891)
Introduction: There are two contradictory opinions regarding the will; one that the will is capable of being trained, the other that it is absolute. The former opinion seems the most plausible, and this will here be treated. “The will,” says Harris, “is the power of a person in the light of reason and with susceptibility to the influence of rational motives, to determine the ends or objects to which he will direct his energy, and the exertion of his energy with reference to the determined end or object.” From this definition it would seem that the will is capable of being trained, and when the two divisions, choice and volition, are given, it seems even more possible. By choice a person decides what object is best, or what course of action he will follow, and by volition he carries into effect the choice, or refuses to do so. Choice is absolute, is necessary; while volition follows from choice, though not necessarily, and in some cases not at all. As choice is the most important of the two, it must receive the most attentions.
Citation: Coburn, Tina Louise. Training of the will. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Will power; Nature; Nurture; Choice; Influence; Theses; Manuscripts (documents)